Learning about sex in later life: sources of education and older Australian adults - Fileborn, B.; Lyons, A.; Hinchliff, S.; Brown, Graham; Heywood, W.; Minichiello, V. (Routledge, 2017)
© 2016 Informa UK Limited, trading as Taylor & Francis Group. This paper examines the preferred sexuality education sources of older Australian adults in later life. Drawing on findings from qualitative interviews with 30 men and 23 women aged 60 years and older, we consider the sources that participants currently use, or would like to use, in seeking information about sex. Where relevant, we examine participants’ experiences of learning about sex in later life using different sources, and the impact these had on their sexual expression, pleasure and well-being. Preferred sources of information include the Internet, the media, health care providers, books and workshops or discussion groups. A substantial number of participants did not actively seek information on sex. For those who had, these educational endeavours could profoundly s hape their sexual practices. As such, learning about sex should be viewed as a lifelong endeavour. Our findings carry important implications for the development and delivery of sexuality education for older adults.